2009
DOI: 10.1073/pnas.0812797106
|View full text |Cite
|
Sign up to set email alerts
|

Location of chloride and its possible functions in oxygen-evolving photosystem II revealed by X-ray crystallography

Abstract: The chloride ion, Cl ؊ , is an essential cofactor for oxygen evolution of photosystem II (PSII) and is closely associated with the Mn 4Ca cluster. Its detailed location and function have not been identified, however. We substituted Cl ؊ with a bromide ion (Br ؊ ) or an iodide ion (I ؊ ) in PSII and analyzed the crystal structures of PSII with Br ؊ and I ؊ substitutions. Substitution of Cl ؊ with Br ؊ did not inhibit oxygen evolution, whereas substitution of Cl ؊ with I ؊ completely inhibited oxygen evolution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(151 citation statements)
references
References 39 publications
7
142
1
1
Order By: Relevance
“…K-851 is very important for the maintenance of the photosynthetic activity as a whole (Dwivedi et al 1995). Furthermore, a small fraction of non-protein-bound Car serves as antioxidant in the lipid phase of photosynthetic membranes (Havaux et al 2004; Kawakami et al 2009) as well as degradation of D1 polypeptide, leading to the inactivation of the PSII reaction center (Zlatev 2009). In an earlier study, we have also demonstrated that salt exposure in Brassica juncea varieties causes reduction in D1 protein (Mittal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K-851 is very important for the maintenance of the photosynthetic activity as a whole (Dwivedi et al 1995). Furthermore, a small fraction of non-protein-bound Car serves as antioxidant in the lipid phase of photosynthetic membranes (Havaux et al 2004; Kawakami et al 2009) as well as degradation of D1 polypeptide, leading to the inactivation of the PSII reaction center (Zlatev 2009). In an earlier study, we have also demonstrated that salt exposure in Brassica juncea varieties causes reduction in D1 protein (Mittal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies conducted in vivo have shown that drought stress causes considerable damage to the oxygen-evolving center (OEC) coupled with PSII (Kawakami et al 2009) as well as degradation of D1 polypeptide, leading to the inactivation of the PSII reaction center (Liu et al 2006;Zlatev 2009). The changes lead to the generation of reactive oxygen species (ROS), which ultimately causes the photoinhibition and oxidative damage (Ashraf 2009;Gill & Tuteja 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One should note that chloride depletion leads to the formation of protein-bound Mn 2+ (36) possibly facilitating this reaction. Additionally, it is possible that chloride depletion perturbs a proton exit pathway (37). Such disruption could give rise to long-lived higher S states (38,39) that may increase the probability of the release of partially oxidized water intermediates.…”
Section: Psii Electron Donor Side Ros Production By Incomplete Water mentioning
confidence: 99%
“…Drought disturbs this balance in rice plant especially in the flag leaf. It also causes damage to oxygen evolving center (OEC) located in PSII (Kawakami et al, 2009) and degradation of D1 polypeptide (subunit of the PS II reaction center) leading to the inactivation of PSII reaction complex (Liu et al, 2006;Zlatev, 2009). Such inactivation leads again to the production of ROS, which further leads to photo-inhibition and oxidative damage (Ashraf, 2009;Gill and Tuteja, 2010).…”
Section: Effect Of Drought On Rice Plantmentioning
confidence: 99%